2011
DOI: 10.1152/ajpendo.00090.2011
|View full text |Cite
|
Sign up to set email alerts
|

Apelin and the proopiomelanocortin system: a new regulatory pathway of hypothalamic α-MSH release

Abstract: Neuronal networks originating in the hypothalamic arcuate nucleus (Arc) play a fundamental role in controlling energy balance. In the Arc, neuropeptide Y (NPY)-producing neurons stimulate food intake, whereas neurons releasing the proopiomelanocortin (POMC)-derived peptide ␣-melanocyte-stimulating hormone (␣-MSH) strongly decrease food intake. There is growing evidence to suggest that apelin and its receptor may play a role in the central control of food intake, and both are concentrated in the Arc. We investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 69 publications
6
35
1
Order By: Relevance
“…4A). The relative expression of apelin mRNA was increased by about 1.5-fold, similar to that observed at the protein level in obese/diabetic mice (42), demonstrating that this overexpression of apelin in normal mice corresponds to the level found in pathological conditions. To identify the impact on glucose homeostasis, we performed insulin tolerance test (ITT).…”
Section: Figsupporting
confidence: 78%
See 3 more Smart Citations
“…4A). The relative expression of apelin mRNA was increased by about 1.5-fold, similar to that observed at the protein level in obese/diabetic mice (42), demonstrating that this overexpression of apelin in normal mice corresponds to the level found in pathological conditions. To identify the impact on glucose homeostasis, we performed insulin tolerance test (ITT).…”
Section: Figsupporting
confidence: 78%
“…On the contrary, obese/ diabetic mice fed a HFD show a disruption of circadian apelin regulation (11). Then, over-increased hypothalamic apelin expression observed in obese/diabetic (11,42) is associated to abnormal regulation of glycemia (11). To reinforce this hypothesis, an icv injection of a high dose of apelin (used in this study and similar to that observed in obese/diabetic mice) in normal mice induces fasted hyperglycemia and insulin resistance (11), characterizing a type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some studies reported i.c.v administration of apelin-13 decreases food intake in animal models (11,25). Reaux-Le Goanzigo et al (26) revealed that K17F, a known active apelin fragment levels are elevated in POMC neurons of ARN leads to α-MSH release in an autocrine manner decreasing the food intake while R10F inactive form of apelin has not generated this effect.…”
Section: Discussionmentioning
confidence: 99%